2017
DOI: 10.1017/s0960258517000071
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory and seed dispersal effectiveness in twoMiconia(Melastomataceae) species from ferruginouscampo rupestre

Abstract: Seed dispersal effectiveness (SDE) is a useful framework to explore the evolutionary and ecological consequences of seed dispersal to plant fitness. However, SDE is poorly studied in tropical open grasslands. Here, we studied both quantitative and qualitative components of SDE in two species of Miconia (Melastomataceae) from ferruginous campo rupestre, a vegetation highly threatened by mining activities. We determined fruit traits and fruit availability and found that fruits of both species are produced in tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…They can ingest whole fruits and effectively disperse seeds within their feces, but they also discard diaspores under parent plants by squeezing out the seeds during fruit handling or by dropping partially consumed fruits containing seeds. In fact, these patterns of fruit handling by birds have been previously documented for other Miconia species [ 28 , 30 , 38 ]. Moreover, we showed that most diaspores falling under parent plants comprise cleaned seeds ejected from the pulp or seeds inside the partially defleshed fruits.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…They can ingest whole fruits and effectively disperse seeds within their feces, but they also discard diaspores under parent plants by squeezing out the seeds during fruit handling or by dropping partially consumed fruits containing seeds. In fact, these patterns of fruit handling by birds have been previously documented for other Miconia species [ 28 , 30 , 38 ]. Moreover, we showed that most diaspores falling under parent plants comprise cleaned seeds ejected from the pulp or seeds inside the partially defleshed fruits.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, rodents and marsupials also consume Miconia fruits, acting as predators and seed dispersers [ 34 36 ]. Spontaneous germination of Miconia seeds within fruits is unlikely to occur [ 37 ], thus seed release from fleshy pulp by birds [ 37 , 38 ], small mammals [ 34 , 36 ] and ants [ 31 , 32 ] is essential for successful germination. Therefore, Miconia comprise an ideal model to explore the consequences of variation in diaspore handling by birds for secondary removal by ground-dwelling fauna.…”
Section: Introductionmentioning
confidence: 99%
“…In that context, the large seed size of the plant suggests that the identity of the dispersal vector in this example is important according to the functional groups we propose ( Table 1 ) ( McConkey et al 2018 ). By contrast, SDE of a suite of bird species was studied for two Miconia species in Brazil ( Santos et al 2017 ). Although the birds varied in the quantity of seeds they dispersed, they did not vary in quality of dispersal ( Santos et al 2017 ).…”
Section: Meaningful Functional Groups In Seed Dispersal Ecologymentioning
confidence: 99%
“…By contrast, SDE of a suite of bird species was studied for two Miconia species in Brazil ( Santos et al 2017 ). Although the birds varied in the quantity of seeds they dispersed, they did not vary in quality of dispersal ( Santos et al 2017 ). Miconia species with their small seeds and large disperser suites (e.g.…”
Section: Meaningful Functional Groups In Seed Dispersal Ecologymentioning
confidence: 99%
“…Moreover, species with similar SDE values suggest that these have similar consequences for the interaction, and may be thus considered functional equivalent. 7 Despite the increasing number of studies assessing quantity and quality components of SDE in birds, 1317 studies have only made qualitative judgements about whether bird species are functional equivalent, based on the relative position and clustering of species onto the SDE landscape. 12,14,18 Therefore, a method to identify functional equivalent species within frugivore assemblages is still lacking.…”
Section: Introductionmentioning
confidence: 99%